Endoscopic resection yields reliable outcomes for small rectal neuroendocrine tumors. Issue 4 (22nd January 2014) - Jeon, Joon Han; Cheung, Dae Young; Lee, Seong Jin; Kim, Hyun Jin; Kim, Hye Kang; Cho, Hyung Jun; Lee, In Kyu; Kim, Jin Il; Park, Soo‐Heon; Kim, Jae Kwang
<x xml:space="preserve">Abstract</x> Background and Aim We analyzed the characteristics of gastrointestinal neuroendocrine tumors and examined the outcomes and safety of modalities in rectal neuroendocrine tumors. Methods Between 2007 and 2011, a total of 91 patients with gastrointestinal neuroendocrine tumors were retrospectively reviewed in terms of the characteristics of tumors. Results Sixty‐six patients had rectal neuroendocrine tumors and underwent endoscopic mucosal resection (EMR, n = 29), endoscopic submucosal dissection (ESD, n = 23), or transanal endoscopic microsurgery (TEM, n = 14). The complete resection rate was higher in the ESD group (82.7%) and in the TEM group (100%) compared to the EMR group (65.5%) (P < 0.046). The complication rate was higher in the ESD group (47.8%) than in the EMR group (18.5%) (P = 0.003). No local tumor recurrence was observed in all patients, regardless of the procedure, during the median follow‐up period of 21.5 ± 13.5 months. Conclusions ESD achieved a higher complete resection rate than EMR and comparable to TEM. Tumor recurrence was not observed in the endoscopic resection and TEM groups, regardless of the completeness of resection. Small neuroendocrine tumors of the gastrointestinal tract can be managed reliably with both endoscopic resection and TEM.